(untitled) (Advances in Applied Mathematics and Mechanics, 2018)
In this paper we extend the idea of interpolated coefficients for a semilinear problem to the quadratic triangular finite volume element method. At first, we introduce quadratic triangular finite volume element method with interpolated coefficients for a boundary value problem of semilinear elliptic equation. Next, we derive convergence estimate in H^1-norm, L^2-norm and L^∞-norm, respectively. Finally, an example is given to illustrate the effectiveness of the proposed method.